品德教育現況及因應十二年國教課程改革之調查研究 Survey on Current Implementation of Character and Moral Education and Response to the Curriculum Reform of 12-Year Basic Education in Taiwan - 劉秀嫚 Show-Mann Liou; 李琪明 Chi-Ming Lee; 陳延興 Yen-Hsin Chen; 方志華 Chih-Hua Fang (National Taiwan Normal University, 2015)
本研究針對525 位學校教育人員、學生家長與民間團體代表進行全國性問卷調查，以瞭解其對於我國品德教育實施現況與問題及面臨十二年國教課程改革之看法。結果顯示：一、品德教育在各教育階段採多元但隨機方式實施，其中個人品德修養與團體規範的教育成效尚佳，但較缺乏公民意識與道德思辨能力之養成；二、品德教育實施之主要困難來自媒體與家庭負面影響，以及師生未予以積極重視；三、受試者對於應著重的品德核心價值與道德議題有所共識；四、單獨設科為多數教育人員與家長期望之品德課程模式；五、十二年國教品德教育須強化的配套措施含師資、教材、網路資源、行政支援與親職教育等。最後，根據分析結果，本研究提出相關的討論與初探性的建議。 A national survey of 525 educators, parents, and civic groups was conducted to determine their perception of the status quo of character and moral education in Grades 1 to 12 as well as their suggestions for the curriculum reform of 12-year basic education. The results indicate that (1) the implementation of character and moral education is diverse and nonsystematic, (2) negative influences of media and family and the ignorance of teachers and students are among the major difficulties in implementing moral and character education, (3) a consensus on the core values and moral issues that should be addressed in 12-year basic education has been attained, (4) most educators and parents prefer that character and moral education be taught as a timetabled subject, and (5) accompanying measures related to the implementation of 12-year basic education include teacher education, instructional materials, Internet resources, administrative support, and parent education. Finally, the results are discussed, and preliminary recommendations for character and moral education in 12-year basic education are proposed.